PROCEDURES OF ALLOCATING SOCIAL SUPPORT BENEFITS IN THE POLISH LEGAL ORDER – AN OVERVIEW OF RELATED ISSUES - Marta, Kopacz (Anales Universitatis Apulensis Series Jurisprudentia, 2012)
The objective of this article is to present basic mechanisms used by the Polish legislator in developing procedures related to granting of social support benefits. The object of analysis included regulations governing the procedure related to granting of housing allowances, family benefits and benefits from the alimony fund. The procedures are characterised with significant decentralisation of regulations, whose sources are both regulations of the Code of administrative procedure, detailed regulations and executive acts. Despite certain differences in legal institutions used by the legislator, the procedures are constructed in compliance with one scheme based above all on very high activity of the applicant to demonstrate his or her fulfilment of premises required for granting of the applied for benefit. Keywords: social support – administrative procedure – housing allowances – alimony fund benefits – family benefits – decentralisation of regulations.